Science, its publics and new media: Reflecting on the present and future of science communication - Dominique Brossard (Mètode Science Studies Journal: Annual Review)
Scientific journalism faces the challenge of adapting not only to new formats but also to new information exchange dynamics. New online platforms, making it easier to access and produce scientific content, are forcing science publics to evolve. The online environment has turned into science communication reality, and both scientists and communicators must adapt to it. This paper discusses these changes and their implications for science journalism and an informed citizenry.